2021
DOI: 10.1007/s00248-021-01688-w
|View full text |Cite
|
Sign up to set email alerts
|

Plant Compartments and Developmental Stages Modulate the Balance between Niche-Based and Neutral Processes in Soybean Microbiome

Abstract: Understanding the dynamics of plant-associated microbial communities within agriculture is well documented. However, the ecological processes that assemble the plant microbiome are not well understood. This study elucidates the relative dominance of assembly processes across plant compartments (root, stem, and leaves) and developmental stages (emergence, growth, flowering, and maturation). Bacterial community composition and assembly processes were assessed using 16S rRNA gene amplicon sequencing. Null models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 76 publications
(88 reference statements)
2
22
0
1
Order By: Relevance
“…1 ). These results are in agreement with earlier reports concerning succession of microbial communities in the phyllosphere [ 8 , 41 , 42 ]. A more detailed look at the assembled phyllopshere microbiome through developmental aging revealed that the core microbiome, composed mostly of Firmicutes and Proteobacteria, was altered in the microbial communities across development, suggesting that changes in the conditions required for survival, succession, persistence, and colonization of different microbial taxa, may occur during plant development and growth.…”
Section: Discussionsupporting
confidence: 94%
“…1 ). These results are in agreement with earlier reports concerning succession of microbial communities in the phyllosphere [ 8 , 41 , 42 ]. A more detailed look at the assembled phyllopshere microbiome through developmental aging revealed that the core microbiome, composed mostly of Firmicutes and Proteobacteria, was altered in the microbial communities across development, suggesting that changes in the conditions required for survival, succession, persistence, and colonization of different microbial taxa, may occur during plant development and growth.…”
Section: Discussionsupporting
confidence: 94%
“…Analysis of the bacterial phyllosphere community dynamics throughout plant developmental stages revealed significant changes to community richness and diversity ( Figure 1 ). These results are in agreement with earlier reports concerning succession of microbial communities in the phyllosphere (Wagner et al, 2016; Manching et al, 2018; Moroenyane et al, 2021). A more detailed look at the assembled phyllopshere microbiome through developmental aging revealed that the core microbiome, composed mostly of Firmicutes and Proteobacteria, was altered in the microbial communities across development, suggesting that changes in the conditions required for survival, succession, persistence, and colonization of different microbial taxa, may occur during plant development and growth.…”
Section: Discussionsupporting
confidence: 94%
“…Bacterial communities of different ecological niches were assembled under the effect of environmental filtering, ecological drift, and dispersal limitations ( Nemergut et al, 2013 ; Moroenyane et al, 2021 ). However, there is still a lack of understanding of these processes.…”
Section: Discussionmentioning
confidence: 99%